2005
DOI: 10.1002/nau.20130
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing self‐perceived disease severity in women with stress urinary incontinence combined with or without urge incontinence

Abstract: Our results suggest that the frequency of UI episodes and the volume of urine loss are associated with PPDS. In addition, the I-QoL scores deteriorated significantly as the PPDS of incontinence increased. Thus, PPDS may impact on the QoL of women with stress UI combined with or without urge UI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 25 publications
2
14
0
1
Order By: Relevance
“…These women also had a more negative perception of the impact caused by UI when compared to the other groups (Table 4) which corroborates to the results observed in the literature 6,7,11,13,17,36 . This may be due to the fact that the women suffer from a combination of SUI (urine loss during activities that increase intra-abdominal pressure) and OB symptoms (urgency, urge-incontinence, nocturia and increased frequency).…”
Section: Quality Of Life Among Women With Urinary Incontinencesupporting
confidence: 90%
See 3 more Smart Citations
“…These women also had a more negative perception of the impact caused by UI when compared to the other groups (Table 4) which corroborates to the results observed in the literature 6,7,11,13,17,36 . This may be due to the fact that the women suffer from a combination of SUI (urine loss during activities that increase intra-abdominal pressure) and OB symptoms (urgency, urge-incontinence, nocturia and increased frequency).…”
Section: Quality Of Life Among Women With Urinary Incontinencesupporting
confidence: 90%
“…The literature commonly verifies that SUI is the more prevalent among women, varying from 12 to 56%. However, in most studies, the diagnosis is based on clinical complaints 6,11,19,26 . Feldner et al 17 compared clinical history and the urodynamic test and found a sensibility of 57.7% and specificity of 79.1%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More women in our study considered themselves satisfied with the treatment than cured. This fact that some women are satisfied even if not completely cured resonates well with a publication from Oh et al, which reported that the frequency of incontinence episodes and the volume of leakage are the most dominating symptoms related to self-perceived disease (148). Therefore if these symptoms improve, the subjective satisfaction rate will likely improve, even if other symptoms are still present.…”
Section: Paper Isupporting
confidence: 66%